1962
DOI: 10.1037/h0045647
|View full text |Cite
|
Sign up to set email alerts
|

Group creativity under conditions of success or failure and variations in group stability.

Abstract: This study deals with the creativity of groups with a history of success or failure followed by 4 variations of group stability: the addition, replacement, or removal of a member, and a control condition in which the original group composition was maintained. Following an induction of group success or failure, 1 of the 3 variations of group composition change or the control condition was effected. The 64 experimental groups were initially composed of either 2, 3, or 4 persons, depending upon the experimental c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

1972
1972
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 10 publications
0
48
0
Order By: Relevance
“…Investigating creative design teams, Choi and Thompson (2005) point out that most studies (Rogers et al 1961, Goodman and Leyden 1991, Pisano et al 2001, Mathiyalakan 2002) report negative effects of membership change on team performance because they focus on task co-ordination. Building on Ziller's (Ziller et al 1961, 1962, Ziller 1965 research, Choi and Thompson (2005) investigate the effects of membership change on the performance of creative teams, and report that the reduction in level of team familiarity may have a positive impact on the team's performance. Their findings suggest that teams with greater membership change generate more ideas and more varied ideas.…”
Section: Discussionmentioning
confidence: 98%
“…Investigating creative design teams, Choi and Thompson (2005) point out that most studies (Rogers et al 1961, Goodman and Leyden 1991, Pisano et al 2001, Mathiyalakan 2002) report negative effects of membership change on team performance because they focus on task co-ordination. Building on Ziller's (Ziller et al 1961, 1962, Ziller 1965 research, Choi and Thompson (2005) investigate the effects of membership change on the performance of creative teams, and report that the reduction in level of team familiarity may have a positive impact on the team's performance. Their findings suggest that teams with greater membership change generate more ideas and more varied ideas.…”
Section: Discussionmentioning
confidence: 98%
“…Choi and Thompson (2005) addressed group composition vis-à-vis the effects of membership change and the introduction of newcomers in groups. They suggested that membership change might promote creativity in groups by increasing task focus (e.g., Ziller, 1965;Ziller, Behringer, & Goodchilds, 1962) and the heterogeneity of knowledge, perspectives, and viewpoints in a group (e.g., Levine & Choi, 2004;Staw, 1980), and by establishing more dynamic group processes such as minority dissent (e.g., Nemeth, 1992;Nemeth & Owens, 1996). In two laboratory experiments, Choi and Thompson (2005) found that membership change resulted in groups generating ideas that were more fluent and flexible and that the creativity of old-timers in groups was enhanced by the introduction of newcomers.…”
Section: Inputs and Conditionsmentioning
confidence: 98%
“…Studies by Ziller, Behringer, and Goodchilds (1962) and, more recently, by Choi and Thompson (2005) provide evidence that the addition or replacement of a member can aid some elements of creative thought. In the Choi and Thompson study, there were two related tasks (one before and one after the replacement of a single member).…”
mentioning
confidence: 96%